2021
DOI: 10.1021/acs.energyfuels.1c02289
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Shale Wettability Using Calorimetry: Experimental Results and Model

Abstract: Wettability affects the occurrence and exploitation of gas and oil in shale matrices; however, conventional methods for shale wettability evaluation (i.e., contact angle testing, imbibition method, flotation testing, surface tension method, and so forth) have limitations, which, in turn, lead to ambiguous or even contradictory results. Thus, in this paper, the calorimetry method is introduced to evaluate the wettability of shale, and the feasibility of the calorimetry method is discussed. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Moreover, Chen et al developed a predictive model for shale wettability quantification based on calorimetry and wettability experiments (i.e., measurement of heat released or absorbed by oil and water) on shale samples obtained from the Shanxi–Taiyuan formation. The model is given as where Q w and Q o are the water and oil wetting heat, respectively; W p , W d , W s , and W I–S are the pyrite, dolomite, siderite, and illite + smectite contents, respectively; and the term “ I ” represents the relative wettability index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Chen et al developed a predictive model for shale wettability quantification based on calorimetry and wettability experiments (i.e., measurement of heat released or absorbed by oil and water) on shale samples obtained from the Shanxi–Taiyuan formation. The model is given as where Q w and Q o are the water and oil wetting heat, respectively; W p , W d , W s , and W I–S are the pyrite, dolomite, siderite, and illite + smectite contents, respectively; and the term “ I ” represents the relative wettability index.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the models proposed here are expected to give a more representative view of the shale wettability. Moreover, Chen et al 63…”
Section: Discussionmentioning
confidence: 99%
“…58 Figure 8 shows a weak negative correlation between the quartz content and the contact angle, which is similar to that in most previous studies. 4,19 We previously revealed that a significantly negative correlation exists between carbonate minerals and CA, 4 reflecting a strong water-wetness for carbonates. However, high siderite content (such as sample M-14 in this study) can lead to a strong oil-wet tendency.…”
Section: Mineralogical Compositionmentioning
confidence: 99%
“…Similarly, if the volume or mass percentage of shale minerals is obtained by X-ray diffraction, the pore parameters are obtained by fluid adsorption or injection methods (such as low-temperature N 2 /CO 2 adsorption, mercury intrusion porosimetry, etc. ), and the TOC content is measured by a carbon/sulfur analyzer, especially the wettability index adopts the composite (or volume) contact angle (considering the whole rock rather than a single test surface) or even any one of the wettability evaluation indexes from spontaneous imbibition, 4 calorimetry, 19 or moisture-equilibrated method. 20 Furthermore, the corresponding triangle method for evaluating whole-rock wettability can also be established by referring to the above workflow.…”
Section: Evaluation and Prediction Of Shale Heterogeneous Wettabilitymentioning
confidence: 99%
“…Compared with the multiple uplifts and reverses of strata and clockwise transgressive changes, the Wenxian shale exploration block gradually deposited Benxi-Taiyuan-Shanxi-Shihezi Formation (Li et al, 2021). Among them, Taiyuan Formation, which developed shale, limestone, sandstone and coal seam and Shanxi Formation, which developed shale, siltstone, medium-grained sandstone and coal seam (Chen et al, 2016(Chen et al, , 2021aLiu et al, 2016) are the target formation (Figure 1(a)).…”
Section: Geological Settingmentioning
confidence: 99%